HUBUNGAN PERILAKU 3M DENGAN KEBERADAAN JENTIK NYAMUK DI DUSUN TEGAL TANDAN, KECAMATAN BANGUNTAPAN, KABUPATEN BANTUL YOGYAKARTA - Handari, Murgi; Kadar, Abdul (STIKES Wira Husada Yogyakarta, 2017)
ABSTRACT Dengue Hemorrhagic Fever (DHF) is a disease that is still a public health problem and is endemic in most districts / cities in Indonesia. Knowing the behavior of the 3M community relations with the existence of larva in DusunTegal Munitions, Bantul, Yogyakarta. Knowing the behavior of the 3M community relations with the existence of larva in DusunTegal Munitions, Bantul, Yogyakarta. This research is an analytic observational study using cross sectional approach. Sampling in this study using proportional cluster random sampling of 82 respondents.Pengoahan and data analysis using a computerized system with Chy-square test. Based on statistical test by using chy-square test 3Ms relationship with the existence of larva behavior is to close water reservoirs (p = 0.003, PR = 1.727, CI = 1.198 to 2.489) drain water reservoirs (p = 0.004, PR = 1.804, CI = 1.373 to 2.370) bury (p = 0.722, PR = 1.179, CI = 0.435 to 3.198). There is a close relationship habits water reservoirs with the presence of larva in Dusun Tegal Munitions, Bantul, Yogyakarta. There is a relationship habits deplete water reservoirs with the presence of larva in Dusun Tegal Munitions, Bantul, Yogyakarta. No significant relationship between habitual secondhand goods bury the existence of larva in Dusun Tegal Munitions, Bantul, Yogyakarta. Keywords: the existence of larva, close, drain, buried secondhand goods.